2019
DOI: 10.3389/fnbeh.2018.00333
|View full text |Cite
|
Sign up to set email alerts
|

FEF Excitability in Attentional Bias: A TMS-EEG Study

Abstract: The role of distinct cortical regions in guiding social orienting needs further investigation. Our aim was to explore the contribution of the frontal eye field (FEF) in early orienting of attention towards stimuli with social value. We used a TMS-EEG approach to investigate event related potentials (ERPs; no-TMS block) and TMS evoked potentials (TEPs; TMS block) during the cueing phase of a modified version of the dot-probe task, comparing competing (face vs. house) and not competing (house vs. house) conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 118 publications
(135 reference statements)
2
6
0
Order By: Relevance
“…This indicates that semantic content within images is more consequential than color for producing model outputs and ERP waveforms, given that the scrambled images contained the same colors as unscrambled images in unrecognizable configurations. The research literature on N170 sensitivity to faces, other objects and non-objects is consistent with these observations 4,6,9,28 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This indicates that semantic content within images is more consequential than color for producing model outputs and ERP waveforms, given that the scrambled images contained the same colors as unscrambled images in unrecognizable configurations. The research literature on N170 sensitivity to faces, other objects and non-objects is consistent with these observations 4,6,9,28 .…”
Section: Discussionsupporting
confidence: 80%
“…A consistent finding from event-related potential (ERP) studies concerning face perception is sensitivity of visually evoked N170 to images of human faces [5][6][7][8] . This ERP peak occurs earlier in response to human faces than other objects and typically has greater amplitude at right hemisphere occipitotemporal electrode sites associated with face processing specialization 9,10 . There remains considerable debate in the literature about whether the N170 component is specific to faces or rather represents a response to highly familiar stimuli -of which faces invariably are.…”
Section: Introductionmentioning
confidence: 93%
“…A consistent finding from event-related potential (ERP) studies concerning face perception is sensitivity of visually evoked N170 to images of human faces [5][6][7][8]. This ERP peak occurs earlier in response to human faces than other objects and typically has greater amplitude at right hemisphere occipitotemporal electrode sites associated with face processing specialization [9,10]. There remains considerable debate in the literature about whether the N170 component is specific to faces or rather represents a response to highly familiar stimuli-of which faces invariably are [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 65%
“…This ERP peak occurs earlier in response to human faces than other objects and typically has greater amplitude at right hemisphere occipitotemporal electrode sites associated with face processing specialization [9,10]. There remains considerable debate in the literature about whether the N170 component is specific to faces or rather represents a response to highly familiar stimuli-of which faces invariably are [6][7][8][9][10]. One argument often cited in support of the specificity view is the observation that familiar but non-face objects tend to elicit an N170 later in time than faces do.…”
Section: Introductionmentioning
confidence: 95%
“…Different studies have indeed shown that a dorsal frontoparietal network is globally associated with attention orientation, even if the regions in the system are engaged differently over time and across the hemispheres concerning the type of attention (Chica et al, 2013). Within this framework, attentional performance critically depends on the interaction between PPC and the frontal eye fields, one holding the sensory representation, the other holding a motor representation (Mesulam, 1981; Torriero et al, 2019). In line with our results, Thiel et al (Thiel, Zilles, & Fink, 2004) showed that the specific reorienting attention activity in PCT increased activation in a bilateral frontoparietal network, including left and right intraparietal sulcus, right temporoparietal junction, and left and right middle frontal gyrus in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%